(untitled) (Bangladesh Journal of Infectious Diseases, 2020)
Background: Bangladesh is a highly populated country for that reasonCOVID-19 is highly transmittable infection in Bangladesh. Objective: The aim of this study was to identify the nurses’ knowledge and practices regarding prevention and control of COVID-19 infection. Methodology: This cross-sectional study was conducted in Rajshahi Medical College Hospital, Rajshahi, Bangladesh from April to July 2020. The questionnaires were completed and returned by the nurses. Collected data were checked, coded and transferred in to SPSS version 25 for analysis. Frequency, percentage, mean, SD, chi-squire and other statistics were calculated. Result: The knowledge and practices scores were categorized into good (≥80%), fair (59-79%), and poor. The result shows that majority of the respondents 83.4% were female and 16.6% were male. 0nly 8.68% took training on COVID-19. More than half of the respondents (52.11%) took information from social media and 7.89% from seminars and workshops. Nearly two third percent nurse’s possessed (73.42%) good knowledge about COVID-19and 17.63% had fair knowledge.73.42% nurses had good practices, 21.84% fair practices and8.68% poor practices. There is a significant relationship between Nurses’ knowledge and practices (p=0.01). Conclusion: In conclusion effective and appropriate health education and training programs improve COVID-19 knowledge and maintenance of safe practices. Safe practices lead to prevent spread of COVID-19 infection from patient to nurses and nurse to patient. Bangladesh Journal of Infectious Diseases, October 2020;7(suppl_2):S27-S33